Relationship between volatile compounds of Picea likiangensis var. linzhiensis cone and host selection of Dioryctria abietella. Issue 3 (7th September 2020) - Tang, Xiaoqin; Gao, Tan; Lu, Jie; Hong, Dawei; Tong, Xianming; Ren, Yihua
Abstract: This study aimed to determine the relationship between volatile compounds of Picea likiangensis var. linzhiensis cone and host selection of Dioryctria abietella . During the infestation of P. likiangensis var. linzhiensis by D. abietella, their cones and branches emitted volatile compounds, which were extracted using CH2 Cl2 extraction and XAD2 adsorption methods, and were analyzed using gas chromatography–mass spectrometry. Before and after overwintering, D. abietella larva preferred annually infested cones and their extracts, and adult D. abietella preferred to lay eggs on annually infested cones and healthy cones of the year, and the oviposition rate of adult D. abietella was 72% on branches with healthy cones of the year, and no egg was laid on branches with annually healthy cones or branches without cones. The volatile compounds after infestation, α‐ and β‐pinene, were significantly higher in cones than those in other tissues; however, myrcene in cones was significantly lower than those in other tissues. The annually infested cones produced β‐caryophyllene and (1S)‐(‐)‐β‐pinene, while the annually healthy cones and branches produced myrcene and 3‐carene. The annually infested cones and their extracts attracted D. abietella larvae, while that of healthy cones and annually infested cones attracted the adults, indicating that the terpene compounds: α‐pinene, β‐pinene, (1S)‐(‐)‐β‐pinene, limonene, and β‐caryophyllene are attractive to D. abietella, and the terpene compounds—myrcene and 3‐carene—from the branch tissues may be repulsive to D. abietella . Abstract : Research Highlights: 1. α‐pinene, β‐pinene, (1S)‐(‐)‐β‐pinene, limonene, and β‐caryophyllene are attractive to Dioryctria abietella . 2. Myrcene and 3‐carene—from the branch tissues may be repulsive to D. abietella .